Titi mentawai: Refutation of the oldest mentawai tattoos in the world - Tulius, Juniator (Jurnal Penelitian Humaniora, 2024)
Mentawai traditional tattoos are often claimed to be the oldest in the world, sparking debates among academics and controversies within the Mentawai community. This study aims to evaluate such claims by analyzing their theoretical and empirical foundations. A qualitative descriptive method was used, incorporating literature reviews from various sources, including Ady Rosa's thesis and prior research reports. The findings reveal that, while Mentawai tattoos are among the oldest traditions characterized by simple motifs and unique techniques, no historical evidence supports the claim that they are the oldest globally. This conclusion underscores the need for critical examination of cultural claims to prevent misinterpretation or misuse in public policy. The study emphasizes that while Mentawai tattoos hold significant historical and aesthetic value, the assertion of their primacy as the oldest tattoos lacks scientific support.